Bitdefender: Hacked Off!. Issue 10 (October 2019) - Unknown
Abstract : Cyber security professionals are profoundly concerned about the vulnerability of their organisations to attack, but are too understaffed and under-resourced to prevent it. And these fears are well-founded, in what is shaping up to be a bumper year for breaches.